El rol de la inversión pública: El caso de Bolivia - Samuel Alarcón Gambarte (Institute for Advanced Development Studies (INESAD), 2020)
– Since 2006, Bolivia began an intensive public investment program under its development plan. Fourteen years later, I analyze the role of this expansionary fiscal policy. In this regard, I develop a Dynamic Stochastic General Equilibrium Model for a small, open and developing country. Among the main results, I highlight that public investment has two roles in the Bolivian economy: positive externality and opportunity cost. First, an increase in public investment generates a positive externality allowing higher levels of economic growth as well as turns into a mechanism to cushion the negative effects of export price shocks. Second, the intensive use of resources for public investment has a crowding out effect on private investment, and deteriorates the public finances in the medium term with the increase of both public debt and fiscal deficit.
Keywords: E62; H5; E32; 330; Public investment; fiscal policy; business cycles; DSGE